(untitled) (Medico Legal Update, 2021)
Family planning (FP) including vasectomy has positive effects in terms of viable socio-economic development and in reducing maternal deaths. The percentage of married men who use condoms (3%) is higher than the percentage who choose vasectomy (less than 1%). The study was conducted in the Madiun town administration using a community-based cross-sectional study design. The town is found in East Java Province, Indonesia. The total sample of this study is 323 married man with fixed disease sampling. Age of wife, wife’s support for vasectomy family planning, access to vasectomy family planning health services and availability of health resources and health infrastructure for vasectomy family planning relates to the selection of men to use vasectomy. In general, vasectomy is seen as one of the least preferred method of family planning and is associated with fear and weakness.